Diffuse Large B Cell Lymphoma Mimicking Granulomatosis with Polyangiitis - Mohammad E. Naffaa; Alexander P. Rozin; Netanel Horowitz; Ofer Ben-Itzhak; Yolanda Braun-Moscovici; Alexandra Balbir-Gurman (Case Reports in Rheumatology)
In a patient with systemic multiorgan disease with overlapping features, the differential diagnosis included infectious diseases, malignancies, and systemic autoimmune or inflammatory diseases. We present an unusual case of a young male with B cell lymphoma who presented with symptoms mimicking systemic vasculitis and review the existing literature.